(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the characteristics of studies on ranula treatment and to summarize the reported outcomes of different treatment modalities. Methods: A scoping review was conducted following the PRISMA-ScR approach. Studies were searched in PubMed, Google Scholar, the Hanoi Medical University library, and Vietnamese medical journal sources. Eligible studies were clinical studies published from January 2010 to December 2025, available in English or Vietnamese full text, and reporting treatment methods and outcomes for ranula. Data were extracted and narratively synthesized according to treatment modality. Results: Of 357 initially identified records, 15 studies involving 336 patients were included. 3 main treatment modalities were identified: surgery, OK-432 sclerotherapy, and Bleomycin sclerotherapy. Surgery was the most frequently reported approach (202 patients), with a recurrence rate of 17.3% and a complication rate of 5.9%. Surgical techniques involving sublingual gland excision, either alone or combined with cyst excision, tended to have lower recurrence rates than gland-preserving procedures. OK-432 was used in 51 patients, with a recurrence rate of 39.2%; complications were mainly local inflammatory reactions. Bleomycin was used in 83 patients, with a recurrence rate of 22.9%, and complications were generally mild and transient. Conclusion: Current evidence suggests that surgery, particularly sublingual gland excision, provides the most reliable recurrence control. OK-432 and Bleomycin sclerotherapy may be considered in selected cases, especially for small lesions or when a minimally invasive approach is preferred. Treatment selection should be individualized according to ranula type, lesion size, extent, and previous treatment history.